The struggle within: ‘Moral Crisis’ on the Ottoman homefront during the first world war - Oğuz, Çiğdem. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2018., 2018)
This study focuses on the issue of a “moral crisis” which was a widely discussed topic among the Ottoman intelligentsia. Moving on from the common view that the “moral crisis” reached a peak during the First World War, this study investigates how morality was related to the war and the preconditions that created the perception of a crisis in morality. The study argues that morality was a contested space among the intellectuals and explains how rival ideologies set forth their political positions depending on diﬀering understandings of morality. For the state, on the other hand, moral decline became a matter of national security during the war. The study demonstrates how wartime rivalries were reflected in the cultural sphere through morality discourses. In public opinion and political circles, immorality was generally considered a social problem that had been imported from European countries. At the social level, the study focuses on family, women, and morality related crimes with an emphasis on the impact of war on traditional family order. e dissertation sheds a light on the place of morality in lawmaking processes, the ideas of reform and progress, and plans for a new society. It also suggests the historical background of contemporary debates on morality vis-à-vis lifestyle, identity, and the impact of moral understanding on the formation of political identity.
Keywords: Turkey -- Social policy -- Moral and ethical aspects.